Associations of Plasma Fatty Acid Patterns During Pregnancy With Gestational Diabetes Mellitus - Li, Peiyun; Hu, Shan; Zhu, Yalun; Sun, Taoping; Huang, Yue; Xu, Zihui; Liu, Hongjie; Luo, Cheng; Zhou, Shiqiong; Tan, Aijun; Liu, Liegang (Frontiers in Nutrition, 2022)
Background: Limited studies have explored the difference of fatty acid profile between women with and without gestational diabetes mellitus (GDM), and the results were inconsistent. Individual fatty acids tend to be interrelated because of the shared food sources and metabolic pathways. Thus, whether fatty acid patters during pregnancy were related to GDM odds needs further exploration. Objective: To identify plasma fatty acid patters during pregnancy and their associations with odds of GDM. Methods: A hospital-based case-control study including 217 GDM cases and 217 matched controls was carried out in urban Wuhan, China from August 2012 to April 2015. All the participants were enrolled at the time of GDM screening and provided fasting blood samples with informed consent. We measured plasma concentrations of fatty acids by gas chromatography - mass spectrometry, and derived potential fatty acid patterns through principle components analysis. Conditional logistic regression and restricted cubic spline model were used to evaluate the associations between individual fatty acids or fatty acid patterns and odds of GDM. Results: Twenty individual fatty acids with relative concentrations ≥ 0.05% were included in the analyses. Compared with control group, GDM group had significantly higher concentrations of total fatty acids, 24:1n-9, and relatively lower levels of 14:0, 15:0, 17:0, 18:0, 24:0, 16:1n-7, 20:1n-9,18:3n-6, 20:2n-6, 18:3n-3, 20:3n-3, 22:5n-3. Two novel patterns of fatty acids were identified to be associated with lower odds of GDM: (1) relatively higher odd-chain fatty acids, 14:0, 18:0, 18:3n-3, 20:2n-6, 20:3n-6 and lower 24:1n-9 and 18:2n-6 [adjusted OR (95% CI) for quartiles 4 vs.1: 0.42 (0.23-0.76), P-trend = 0.002], (2) relatively higher n-3 polyunsaturated fatty acids, 24:0, 18:3n-6 and lower 16:0 and 20:4n-6 [adjusted OR (95% CI) for quartiles 4 vs.1: 0.48 (0.26-0.90), P-trend = 0.018]. Conclusions: Our findings suggested that two novel fatty acid patterns were inversely associated with GDM odds. The combination of circulating fatty acids could be a more significant marker of GDM development than individual fatty acids or their subgroups.